Wasathiyah Islam: The Constellation of Al-Azhar University in Global Geopolitics - Zainal Fanani; Fikri Taufiqur Rohman; Mohammad Fuyudun Niam Imam; Arfan Maskuri (Universitas Muhammadiyah Enrekang, 2024)
Islam Wasathiyah, a concept that emphasizes moderation and balance in the understanding and practice of Islam, has become an increasingly important religious discourse in the context of contemporary global geopolitics. This paper aims to explore the central role of al-Azhar University, Egypt's leading Islamic educational institution, in developing and promoting Islam Wasathiyah amidst complex socio-political dynamics. Using historical and analytical approaches, this paper examines the internal and external factors that drive the emergence of the concept of Islam Wasathiyah, and analyzes al-Azhar's involvement in political contestations in Egypt and the Islamic world in general. Furthermore, this paper outlines the strategies implemented by al-Azhar, especially under the leadership of Grand Sheikh Ahmed al-Tayeb, in campaigning for Islam Wasathiyah through various initiatives, such as international conferences, scientific publications, institutional cooperation, and religious diplomacy. By analyzing al-Azhar's role in facing the challenges of religious extremism and radicalism, this paper contributes to the discussion on the future of moderate Islam and the significance of religious institutions in shaping inclusive and peaceful Islamic discourse and practice. The findings of this study emphasize the importance of al-Azhar's role as a key actor in the global geopolitical landscape, as well as its potential in promoting a balanced and contextual understanding of Islam in facing contemporary challenges.